Prof. Dr. Mohd Nazip Bin Suratman visit IMMB - Ali, Roslina; Idorus, Mohd Yusri (Faculty of Medicine, 2021)
The Faculty of Medicine, UiTM Sungai Buloh welcomed Professor Dr. Mohd Nazip Bin Suratman on his last visit as a Deputy Vice Chancellor (Research & Innovation). This event was held on the 12th November 2021. His arrival was warmly welcomed by a group of Faculty Management Members led by Professor Dr. Ariza Adnan, Deputy Dean (Industry, Community & Alumni Network), Associate Professor Dr. Thuhairah Hasrah Abdul Rahman, Deputy Dean (Research & Innovation), Professor Dr. Rohana Abdul Ghani, Deputy Dean (Postgraduate & Professional Training), Professor Dr. Ahmad Nazrun Shuid, Deputy Dean (Student Affair) and Dr. Heo Chong Chin, Director of Institute of Medical Molecular Biotechnology (IMMB).